Optical beam characterization via phase-space tomography : Doctoral Thesis accepted by the Complutense University of Madrid, Spain /: Doctoral Thesis accepted by the Complutense University of Madrid, Spain. ([2015]) - Cámara, Alejandro
No abstract available